Perception of primary school teachers towards role of creativity in learning: a qualitative study - Sharma, Ekta; Sharma, Sandeep (Creativity Studies, 2025)
Creativity has become one of the most coveted skills in today’s ever-changing world, where the sustainability of an individual is based on his/her creative potential. The need to foster creativity and innovation has long been a priority in the educational and corporate spheres. The current research focuses on perceptions primary school teachers hold regarding creativity and its role in learning, along with the identification of the creative student. The data is collected through focus group discussion. Teachers unanimously accept the role of creativity in enhancing learning and facilitating the child’s overall development. The study could be replicated in different countries, and the gap between perception and reality could be identified. This gap identification could be considered a basis for providing developmental intervention to the teachers to foster creativity among the children and formulate policy for educational management at the school level.